Muscle Cramps: A ‘Complication‘ of Cirrhosis - Paul J Marotta; Ivo W Graziadei; Cameron N Ghent (Canadian Journal of Gastroenterology)
Muscle cramps are a common complaint in clinical practice. They are associated with various metabolic, endocrine, neurological and electrolyte abnormalities. A variety of hypotheses have been generated to explain the cause of muscle cramping, yet none has been able to support a consistent pathophysiological mechanism. Muscle cramps are painful, involuntary contractions of skeletal muscle. They occur frequently in individuals with cirrhosis, regardless of the etiology, and are thought to be a symptom of cirrhotic-stage liver disease. The pathophysiology of these cramps remains elusive; hence, a specific therapy has not been identified. Many therapeutic approaches have been offered, yet their efficacy, safety and mechanism of action remain poorly defined. This review defines muscle cramps and illuminates its prevalence in the cirrhotic individual. Current theories relating to the pathogenesis of muscle cramps are reviewed, and an overview of the various pharmacological agents that have had therapeutic success for this distressing and frustrating symptom is provided.